Implementasi Stop-Motion Animation Untuk Membangun Pemahaman Konsep Siswa pada Materi Listrik Dinamis di SMP - Nurazizah Puspitasari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study explores the process of discovering the concept of dynamic electricity by students through stop-motion animation modeling. The study uses a qualitative approach with a case study design carried out in four stages, namely preparation, introduction to the phenomenon, animation creation, and discussion. Dynamic electricity is a difficult subject in science education because it involves processes that cannot be observed directly, such as electric current and electron flow on a microscopic scale. This condition makes it difficult for students to visualize the process of electric current in real life. Analysis of the stop-motion animations developed by students shows that this modeling is effective in helping students understand most of the concepts of dynamic electricity qualitatively. However, concepts that require mathematical understanding and the use of quantitative data cannot yet be optimally represented through stop-motion animation. Thus, stop motion animation has the potential to become a learning medium that supports conceptual understanding of dynamic electricity, particularly in qualitative aspects.
:: Finalisasi repositori 15 Juli 2026_Kurnadi
Keywords: conceptual understanding; dynamic electricity; stop-motion animation; case study